FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PERMINTAAN BERAS DI KOTA BAUBAU - Hardin, Hardin (Media Agribisnis, 2020)
Rice for people of Baubau town is the first staple food after maize and tubers. While the agricultural sector will not be able to provide food for the people of Baubau including rice, because extensification cannot be carried out. This study aims: (1) Determine the effect of rice, corn, and egg costs, the total population and the level of income of the population affect the rice demanded in Baubau town; (2) Knowing the elasticity value of rice requested in the town of Baubau. The data analysis method used in this study is multiple linear regression analysis while price elasticity and cross elasticity can be obtained from the value of bi in the calculation of SPSS version 22.0. The conclusions of this study: (1) Simultaneously both the price of rice, corn, and eggs, as well as the total population, have a positive and significant effect on the demand for rice in Baubau; (2) Based on the value of price elasticity of 9,124. The meaning of this value is that if the price of rice rises by 1 percent, demand also rises by 9,124% and if it goes down the opposite occurs. Because Ep> 1 results, demand is elastic; (3) The cross elasticity value of corn is 0.327, this means that if for 1 percent of the price of corn, the demand for rice also rises with a value of 0.327%, if a decrease of 1 percent will occur otherwise. The elasticity value of corn prices marked with (+)/positive means that corn is a substitute item from rice. The price of eggs has a cross elasticity of 3.746, this means that if the price of eggs rises by 1%, the demand for rice will increase by 3.746%, and vice versa. The cross elasticity value of the egg price is positive, indicating that the egg is a substitute item from rice, there is a conflict with the existing theory that the egg is a complimentary item and the elasticity value has a sign (-)/negative.  Keywords: Factors, Affecting Rice Demand